Implementation of Principles, Innovations, and Challenges in the Development of Islamic Finance in Indonesia - Wahid, Sahid; Haddade, Abdul Wahid; Syatar, Abdul (Journal of Universal Community Empowerment Provision, 2025)
Islamic finance is an alternative economic system that is growing rapidly in Indonesia, based on Islamic principles such as the prohibition of usury, fairness in transactions, transparency, and social responsibility. This paper examines the main principles of the Islamic financial system, including the prohibition of usury and gharar, as well as the application of ethical and moral values ​​in financial activities. In addition, this article also discusses various innovative Islamic financial products such as sukuk, microfinance, and Islamic insurance, which are designed to meet the needs of the community while still upholding Islamic principles. Despite significant growth, this industry still faces a number of challenges, including limited regulations that support innovation, low public literacy, tight competition with conventional systems, and a lack of competent human resources. Through a descriptive-analytical approach, this study shows that consistent application of Islamic principles, adaptive regulatory support, and increasing human resource capacity are the keys to strengthening and sustaining the Islamic financial system in Indonesia. This research is expected to be an academic contribution to the development of more inclusive and sustainable Islamic economic theory and practice.